FACTORS THAT CONTRIBUTE TO THE ONSET OF SEXUAL ACTIVITY IN ADOLESCENTS: INTEGRATIVE REVIEW - Santos, Taciana Mirella Batista dos; Albuquerque, Lívia Brito Bezerra de; Bandeira, Carolina da Franca; Colares, Viviane Soares de Andrade (Journal of Health Care, 2015)
Introduction: Sexual activity has often happened during adolescence. Adolescents who start this activitytoo early are exposed to risks related to unprotected sexual activity, which can have as consequence anincreasing risk of sexually transmitted infections, teen pregnancy, school dropouts, among others. Thisstudy aims to identify factors associated with early sexual activity among adolescents. Development: Thisis an integrative literature review, which have analyzed 11 of the 717 articles found in the Virtual HealthLibrary. Studies performed with Brazilian adolescents, published between 2003 and 2013 were included.In this review the first sexual intercourse was associated with multiple factors. The most frequently citedwere age, gender and cultural issues, peer influence, religion, family, dating relationships, education andsocioeconomic factor. Conclusion: The existence of intrinsic and extrinsic factors influence the sexualbehavior and should be discussed, especially before the onset of sexual practices.
Keywords: Sexual behavior; sexual education; sexual health; sexism; sexuality